Posmodernisme Kode Visual dalam Iklan Komersial - Ferry Darmawan (MediaTor (Jurnal Komunikasi), 2006)
The development of ads and advertising raise some sociocultural issues concerning the sign being represented, image being constructed, information being delivered, meaning being acquired, and how everything affects perception, understanding, and public behavior. Advertising is attached to the product, offering images as values and moral reference for public. Advertising creates image of a product and assigns social relationship as reflected on status, prestige, and social class. Postmodernism establish a new form of signification: form follows fun. It is not the meaning, but the interplay between signs that considered the most important thing in advertising.